2018
DOI: 10.1002/lno.11006
|View full text |Cite
|
Sign up to set email alerts
|

High resilience of harpacticoid copepods in the landward slope of the Japan Trench against disturbance of the 2011 Tohoku Earthquake

Abstract: On 11 March 2011, an earthquake of magnitude Mw 9.0 known as “the 2011 off the Pacific coast of Tohoku Earthquake” occurred off the coast of Miyagi Prefecture. To assess the effect of the earthquake on the deep‐sea ecosystem, we compared harpacticoid assemblages at six stations (100–6000 m water depth) in the landward slope of the Japan Trench off Sanriku in northeastern Japan. We collected samples at the same locations after 4.5 months (2011) and 1.5 yr (2012) after the earthquake. There were no significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A similar subsurface peak was observed for foraminifera (meiofauna) at nearby sites (3250 -3585 m water depth) following the 2011 turbidity flow (Tsujimoto et al, 2020). These anomalous peaks were attributed to an increase in available carbon, for reasons similar to Heezen et al's hypothesis, but other explanatory variables such as dissolved oxygen could not be ruled out (Kitahashi et al, 2014(Kitahashi et al, , 2016(Kitahashi et al, , 2018.…”
Section: Influence On Productivitymentioning
confidence: 82%
See 1 more Smart Citation
“…A similar subsurface peak was observed for foraminifera (meiofauna) at nearby sites (3250 -3585 m water depth) following the 2011 turbidity flow (Tsujimoto et al, 2020). These anomalous peaks were attributed to an increase in available carbon, for reasons similar to Heezen et al's hypothesis, but other explanatory variables such as dissolved oxygen could not be ruled out (Kitahashi et al, 2014(Kitahashi et al, , 2016(Kitahashi et al, , 2018.…”
Section: Influence On Productivitymentioning
confidence: 82%
“…Three studies evaluating the impact of turbidity flows on the meiofauna and prokaryote communities following the turbidity flow triggered by the 9.0 (Mw) 2011 Tōhoku Earthquake found that in general faunal density was no different after the event, but that vertical distribution in the sediments trended deeper. Kitahashi et al (2014Kitahashi et al ( , 2016Kitahashi et al ( , 2018 conducted studies of the impact on meiofauna along a north (123 -5604 m water depth) and south line (150 -3960 m water depth) in the Japan Trench off the coast of Sanriku. These data, collected 4.5 months and 1.5 years after the turbidity flow, were compared to data collected 24-30 years before the turbidity flow along the same northern line (Shirayama and Kojima, 1994).…”
Section: Influence On Productivitymentioning
confidence: 99%
“…In shallow-water environments where sedimentation rates are higher and physical disturbances more frequent, studies have shown some organisms are able to survive burials between 30 and 50 cm, with the more mobile fauna able to migrate up through the deposited material to the sediment-water interface (Maurer et al, 1986;Nichols et al, 1978). Survival rates are higher if the deposited material is similar to the underly-ing sediment (Kranz, 1974). Organisms tend to be adapted for a particular substrate type and unlike their shallow-water counterparts, deep-sea organisms have evolved to survive very low sedimentation rates, typically 0.1-2.9 cm kyr −1 for the abyssal plain (Stordal et al, 1985;Weaver and Rothwell, 1987).…”
Section: Initial Impacts Of Turbidity Flows On Benthic Communitiesmentioning
confidence: 99%
“…A similar relative abundance response by nematodes and copepods to a turbidity flow disturbance was observed after the Tōhoku earthquake triggered turbidity flow, where nematode densities remained unchanged after the disturbance, but harpacticoid copepod densities were negatively impacted by the disturbance and it wasn't until months to years after the event that they increased (Kitahashi et al 2014(Kitahashi et al , 2018. While annelids, which are often juveniles macrofauna species (Warwick, 1988), were not identified as key taxa contributing to the community structure dissimilarity between time points by 4 years after the disturbance, they had increased in abundance from 10 weeks after the disturbance.…”
Section: Impact Of Turbidity Flow On Meiofauna and Nematode Community...mentioning
confidence: 58%